Fatores ambientais e ocorrência de fungos micorrízicos arbusculares em florestas de ecótono do Leste da Ilha de Maracá, Roraima - Benevides, Oscar Oswaldo Prieto (2020)
This study aimed to evaluate the community of arbuscular mycorrhizal fungi (FMA) in three forest types, and the relationship of these microorganisms with the dominance of P. gracilipes in two seasons (dry and rainy) in eastern Maraca Island, Roraima, northern Brazilian Amazon. For this, soil samples were collected in two seasons, one in the rainy season and the other in the dry season. The samples were collected in 9 plots, in rich areas (FRP), poor areas (FPP) and areas without P. gracilipes (FSP). The soil samples were sieved and evaluated for: chemical and granulometric analysis, density and morphology of spores and identification of FMA. From the morphology data the richness and diversity of species were calculated. From the soil samples collected the trap culture using Urochloa brizantha was also performed, in which the FMA diversity was also evaluated. Root samples in the P. gracilipes field were collected and the rate of colonization by FMA was evaluated. In addition, soil samples of up to 1 meter deep were collected in each forest type for soil type determination. Based on the data obtained, environmental conditions (soil factors, forest types and seasonality) and their relationship with FMA communities were evaluated. A multivariate variance permutation analysis was used to test whether the FMA community composition differed between forest types and seasons. In FRP a higher average content of M.O., pH, P, K, Ca, Mg, H+Al, Fe, Zn, Mn and B were observed compared to FSP. The predominant soil classes in Maracá Island were Argissolos and Plintossolos. The richness of spores in 50 g of soil differed (P < 0,01) between locations and the time of harvest, ranging from nine to 13 in the dry season and five to nine in the rainy season. 18 and 13 FMA species were identified in the dry and rainy seasons, respectively, for spores extracted from the field. In total, 10 species were detected exclusively in trap plants. The FMA communities were coded by members of the Gigasporaceae, Acaulosporaceae and Glomeraceae family. On the other hand, the percentage of mycorrhizal colonization was distinct between seasons, being higher in the dry season (63.69 %) compared to the rainy season (18.7 %). The PERMANOVA test based on data of presence and absence of species indicated that the FMA community differed among all sites and seasons. The RDA analyses indicated that various soil attributes (pH, Fe, Mg and sand content) influenced the richness of FMA species in both seasons. The study concluded that the Maraca ecotonal forests are the habitat of several FMA species and that edaphoclimatic factors influence the composition of the FMA community in this ecosystem. Of the three forest types studied in Maracá, only in the FRP there were unique indicator species (Gigaspora sp.1 and Acaulospora scrobiculata) both in the dry and rainy season, these species could positively influence the dominance of P. gracilipes in this area.